1996
DOI: 10.1046/j.1365-2796.1996.454000.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcific degeneration of the aortic valve in old age: is the development of flow obstruction predictable

Abstract: A time-dependent reduction of the aortic valve flow orifice can be demonstrated in persons representing the general elderly population. The deterioration of aortic valve function within a span of 3 years is neither clinically nor biochemically predictable. A longer follow-up may be necessary to identify the risk factors of aortic valve stenosis in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Some reports shown an association of hyperlipidemia and diabetes with AVC [4,11], whereas others have failed to find this association [2,10]. In our study, we also failed to identify clinical variables associated with advanced AVC except age.…”
Section: Discussioncontrasting
confidence: 82%
“…Some reports shown an association of hyperlipidemia and diabetes with AVC [4,11], whereas others have failed to find this association [2,10]. In our study, we also failed to identify clinical variables associated with advanced AVC except age.…”
Section: Discussioncontrasting
confidence: 82%
“…Although investigations are underway to determine whether statin therapy may prevent or delay disease progression, at present, the mainstay of treatment for severe calcific AS is valve replacement surgery (5). AS is already the most common indication for valve replacement surgery in the US (5), and, given the aging US population, calcific AS is predicted to become an increasing health burden (1,21,22,45). Although several risk factors have been associated with increased prevalence and/or progression of AS, growing evidence suggests that genetic factors also modify susceptibility to congenital and calcific valvular disease (11,16,17,26,27,36,41,42).…”
mentioning
confidence: 99%
“…2,3 The disease shows a progressive course, especially after the threshold to mild aortic stenosis has been crossed. 2,4 Common pathomechanisms of aortic valve stenosis and atherosclerosis have been discussed, and several studies have demonstrated an influence of cardiovascular risk factors on the progression and outcome of aortic valve stenosis, but results have been inhomogeneous as to the relative importance of specific risk factors. [5][6][7][8][9] Several studies have identified the degree of aortic valve calcification as a strong predictor both for the progression and outcome of aortic stenosis.…”
mentioning
confidence: 99%